2009
DOI: 10.1016/j.cell.2009.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Protein Disorder and Interaction Promiscuity Are Widely Associated with Dosage Sensitivity

Abstract: Why are genes harmful when they are overexpressed? By testing possible causes of overexpression phenotypes in yeast, we identify intrinsic protein disorder as an important determinant of dosage sensitivity. Disordered regions are prone to make promiscuous molecular interactions when their concentration is increased, and we demonstrate that this is the likely cause of pathology when genes are overexpressed. We validate our findings in two animals, Drosophila melanogaster and Caenorhabditis elegans. In mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
234
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(269 citation statements)
references
References 47 publications
19
234
0
Order By: Relevance
“…Thereby, caution in interpretation of molecular analysis data and the relationship between cause and effect in cells with unstable genome is needed [5,10,47]. Karyotype-phenotype causality [2,3,5,6], the genome context-dependent antagonistic functional duality of cancer genes [20], potential promiscuous molecular interactions not relevant to normal cellular conditions of dosage-sensitive oncogenes with increments in concentration of protein products [56], and an introduction of a term "good oncogene" [20,57], which describes a gene that is both a marker for favorable survival probability in clinic but one with tumor promoting and transforming properties in experimental settings incline to re-evaluate the dominating concepts in cancer research.…”
Section: Discussionmentioning
confidence: 98%
“…Thereby, caution in interpretation of molecular analysis data and the relationship between cause and effect in cells with unstable genome is needed [5,10,47]. Karyotype-phenotype causality [2,3,5,6], the genome context-dependent antagonistic functional duality of cancer genes [20], potential promiscuous molecular interactions not relevant to normal cellular conditions of dosage-sensitive oncogenes with increments in concentration of protein products [56], and an introduction of a term "good oncogene" [20,57], which describes a gene that is both a marker for favorable survival probability in clinic but one with tumor promoting and transforming properties in experimental settings incline to re-evaluate the dominating concepts in cancer research.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, exogenous Nmnat2 may form a spurious interaction with one or more proteins at the membrane. It has recently been suggested that such interactions are a common cause of toxicity resulting from protein overexpression (64). The lack of gross toxicity in non-neuronal cells may therefore be due to the absence (or low abundance) of a specific interacting protein.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic protein disorder was found to be an important determinant for proteins encoded by these genes, and explained by their inclination to be involved in promiscuous molecular interactions. 115 Regulation of dosage-sensitive genes occurs at the transcriptional, RNA, and protein levels. 116 Recent studies by Suskiewicz and colleagues proposed several possible further mechanisms by which IDPs could be regulated in vivo, 117 where IDPs would be protected from degradation by default (see Fig.…”
Section: Survival Of Idps In the Cellmentioning
confidence: 99%